Square microstrip patch antenna with t-probe fed for wimax applications / Suziana Omar - Omar, Suziana (2017)
This paper concerned on enhancement gain for square microstrip patch antenna using T-probe feeding technique. Air is used as substrate in this proposed design. The thickness of the air-filled substrate, 12mm is presented with equal to 1.